2013
DOI: 10.1002/acr.22036
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of Hip Examination Tests for Femoroacetabular Impingement

Abstract: Objective. To assess the interrater reliability of hip examination tests used to assess femoroacetabular impingement (FAI) among clinicians from different disciplines. Methods. Twelve subjects were examined by 9 clinicians using 12 hip tests drawn from a review of the literature and consultation with experts in hip pain and FAI. Examiners assessed both hips of each subject and were blinded to subject history. The order in which subjects were seen, the order of tests, and order of examination of the 2 hips with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
12
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 36 publications
3
12
0
Order By: Relevance
“…Prior to the study, CR (an experienced researcher and PT) led a training session with 7 PTs and two rheumatologists, which introduced a standardized description of each test, a standardized script for asking patient questions, demonstration of each test, and practice with feedback. In a previously reported interrater reliability study, which included 4 of the 9 PTs participating in the current study, we found overall agreement of 0.76 (0.66-0.91), negative agreement of 0.79 (0.60-0.93), and positive agreement of 0.73 (0.58-0.89), indicating that the test was reliable [31].…”
Section: Accepted Articlesupporting
confidence: 67%
See 2 more Smart Citations
“…Prior to the study, CR (an experienced researcher and PT) led a training session with 7 PTs and two rheumatologists, which introduced a standardized description of each test, a standardized script for asking patient questions, demonstration of each test, and practice with feedback. In a previously reported interrater reliability study, which included 4 of the 9 PTs participating in the current study, we found overall agreement of 0.76 (0.66-0.91), negative agreement of 0.79 (0.60-0.93), and positive agreement of 0.73 (0.58-0.89), indicating that the test was reliable [31].…”
Section: Accepted Articlesupporting
confidence: 67%
“…Physical examination plays an important role in the definition of FAIS and several impingement tests have been described in the literature [16,33,36]. For the current study, we selected the FADIR test because it has been recommended by an international panel of experts [16], is reliable [31,36,33], and commonly used by clinicians [16,30]. However, prevalence of a positive FADIR test in the general population is not well established.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…If muscular restriction is present, specific techniques including stretching, soft-tissue work as well as using the entire ROM in sports-specific tasks during the end phase of rehabilitation should be considered. Articular restriction may be less likely to change with these interventions, and end range loading may even provoke symptoms [46]. This may partly explain why addressing flexibility specifically (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…The participants will have the FABER (Flexion, ABduction, and External Rotation) test and the anterior impingement test at 90 and 120° of hip flexion performed, as described by Ratzlaff et al . 36 A positive test is indicated by pain in the upper/inner thigh or groin.…”
Section: Methodsmentioning
confidence: 99%